Anti-biofilm and anti-adherence activities of Spilanthes acmella leaves extracts towards Streptococcus mutans - Rohazila Mohamad Hanafiah; Siti Sarah Azhar; Luqman Atif Elias; Siti Aisyah Abd Ghafar (Frontiers, 2024)
International Conference on Drug Discovery and Translational Medicine 2018 (ICDDTM '18) “Seizing Opportunities and Addressing Challenges of Precision Medicine”, Putrajaya, Malaysia, 3 Dec - 5 Feb, 2019.